Analisis Sistem Antrian pada Loket Pelayanan Cepat (Fast Track) di Kantor BPJS Kesehatan Cabang Padang - Envi Sari Oktaviani; Dewi Murni (Journal of Mathematics UNP, 2019)
Abstract— Queue is a condition when some persons are waiting for their turn for a service, as often occured at the office of BPJS Kesehatan (Healthcare and Social Insurance Security Agency) in Padang because the presence of large numbers of the customers of JKN-KIS (National Healthcare Insurance – Healthy Indonesians Card) program. This research aimed to know what kind of queuing models already applied and how optimum the performance of the queuing system. This research is an applied research using primary data. The data is analysed by way of calculating the average time of arrival of the customers and average time of services, conducting distribution match test by applying Kolmologrov Smirnov test, and then analysis. The research found that the queuing models being applied are: (M/M8):(GD/∞/∞) and the number of officers at the fast track service counters needs to be increased to be more optimal. Keywords— Queue, Kolmologrov Smirnov Test, Single Channel Single Phase, Multiple Channel Single Phase.